2016
DOI: 10.1016/j.jcmg.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Demographics, Risk Factors, Presentation, and Noninvasive Testing in Stable Outpatients With Suspected Coronary Artery Disease

Abstract: STRUCTURED ABSTRACT Objectives To determine whether presentation, risk assessment, testing choices, and results differ by sex in stable symptomatic outpatients with suspected coronary artery disease (CAD). Background Although established CAD presentations differ by sex, little is known about stable, suspected CAD. Methods Characteristics of 10,003 men and women in the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) trial were compared using chi-square and Wilcoxon rank sum tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 35 publications
8
102
2
2
Order By: Relevance
“…Post-hoc analysis of the PROMISE study, however, identified sex-differences in risk assessment, noninvasive test outcomes and noninvasive test prognostic value, highlighting the importance of sex-specific approaches for the evaluation of CAD 124, 252 . For example, not only were women more likely to be characterized as lower risk by providers and by risk scores despite having a greater number of cardiac risk factors, women were also less likely to have a positive test 252 . The Diamond and Forrester risk score, which classifies chest pain as typical, atypical, and nonanginal, was predictive of a positive test in men but not in women.…”
Section: Stable Ischemic Heart Disease (Sihd)mentioning
confidence: 99%
“…Post-hoc analysis of the PROMISE study, however, identified sex-differences in risk assessment, noninvasive test outcomes and noninvasive test prognostic value, highlighting the importance of sex-specific approaches for the evaluation of CAD 124, 252 . For example, not only were women more likely to be characterized as lower risk by providers and by risk scores despite having a greater number of cardiac risk factors, women were also less likely to have a positive test 252 . The Diamond and Forrester risk score, which classifies chest pain as typical, atypical, and nonanginal, was predictive of a positive test in men but not in women.…”
Section: Stable Ischemic Heart Disease (Sihd)mentioning
confidence: 99%
“…34 The higher burden of nonobstructive atherosclerosis in women may result in negative stress tests and obscure the diagnosis of IHD, underscoring the need for additional diagnostic imaging that reveals the nonobstructive pathophysiological mechanisms of IHD. 30,35 Consequently, the 2014 AHA consensus statement for noninvasive evaluation of woman at risk for IHD recommends testing for the full spectrum of IHD ( Figure 3).…”
Section: 31-33mentioning
confidence: 99%
“…4 All trials, including this cohort, had a low CAD prevalence with overestimation of the individual probability of disease by conventional prediction rules for both men and women. 13,14,22 In CRESCENT, the CAD prevalence was 9% in women, whereas the predicted probability by the Diamond and Forrester method was 38%. For men, the prevalence was 12%, whereas the predicted probability was 54%.…”
mentioning
confidence: 99%